Інтеграція google календаря в медичні інформаційні системи - Бабічева, А. К.; Редін, Д. В. (ХНУРЕ, 2023)
The essence of this study is to determine the prospects for using the Google Calendar service and its integration in modern medical information systems. This analysis aims to draw relevant conclusions about the functions of the service, which can be used in medicine when developing the task of planning and time management. And also the main attention will be focused on how to comprehensively use Google Calendar and the Calendar of the information system